Ethics and Deontology, Training, and Clinical Practice in Orofacial Harmonization - questionnaire design and construction - Silveira, Augusta; Castro , Inês; Almeida, Aline Raybolt dos Santos; Santos , Virgínia; Silva , Isabel; Veiga , Francisco; Guimarães , Maria Inês (Scientific Letters, 2024)
Background: The term "Orofacial Harmonization" is a concept based on the application of clinical and therapeutic procedures that, in synergy with various specialties and areas of Dentistry, aims to promote the aesthetic and functional harmony of the orofacial region. The journey of Orofacial Harmonization began in various areas of Biomedical and Medical Sciences, in addition to Dental Sciences. Areas such as anatomy-physiology, molecular biology, immunohistochemistry, cytogenetics, pharmacology, and medicine are interconnected with the concept of Orofacial Harmonization. Objective: Description of all phases for constructing a research instrument for Oral Health Professionals/Students. We present the final version of the questionnaire already submitted and approved by the Ethics Committee. Methods: The present investigation is based on the construction of a Research Instrument. Initially, the construct and dimensions were defined, followed by the development of a pool of items. The type of scale was chosen. Content analysis was conducted with recognized experts in this research area. The experts provided their opinions on dimensions, appropriateness of formulation, comprehension of the questions, degree of pertinence, relevance, and the use of scales. Results: Six stages were conducted: objectives’ recognition, literature review, question development, expert review, pilot testing, and ethical approval. The final research instrument consists of 3 parts: collection of sociodemographic variables (a total of 5 questions), a specific questionnaire on training and professional practice in Orofacial Harmonization (a total of 30 questions), and a questionnaire on ethics and deontology in Orofacial Harmonization (a total of 17 questions). Conclusions : Orofacial Harmonization represents a growing area of interest and expansion in Dentistry, reflecting an emergent need to understand the ethical, deontological, and professional practice perspectives associated with this field of knowledge. The relevance of this questionnaire lies in its ability to capture the opinions, experiences, and expectations of professionals and future professionals.